Hydrothermal growth of few layer 2H-MoS2 for heterojunction photodetector and visible light induced photocatalytic applications. Issue 12 (4th March 2016) - Midya, Anupam; Ghorai, Arup; Mukherjee, Subhrajit; Maiti, Rishi; Ray, Samit K.
Abstract : Template-free, bottom-up synthesized, micron sized few layer 2H-MoS2 for photodetector and photocatalytic applications. Abstract : The present low yielding growth techniques of semiconducting 2H phase molybdenum disulfide (MoS2 ) hamper its widespread applications. In this article, we report a novel hydrothermal chemical approach to synthesize micron sized few layer 2H-MoS2 on a large scale. Sodium molybdate and ammonium thiocyanate have been used as precursors to obtain template-free 2H-MoS2 in solution. Detailed microscopic and spectroscopic characterizations reveal that the bottom-up synthesized few layer MoS2 flakes are highly crystalline having the hexagonal 2H phase. Photodetector devices comprising a p-type silicon (p-Si)/n-MoS2 heterostructure have been fabricated for the first time using solution processed 2H-MoS2 synthesized by the bottom up approach. The heterojunction diode exhibits a high rectification ratio (>10 3 ) with broad band photoresponse over the visible range. Because of the visible light photoresponse, as-synthesized MoS2 along with reduced graphene oxide (MoS2 –RGO hybrids) have been utilized to study the potential of this two dimensional (2D) heterostructure for visible light driven photocatalytic Rhodamine B dye degradation. This study demonstrates the potential of solution processed MoS2 for integration with silicon and growth of 2D heterostructures for visible light induced multifunctional applications.